2016
DOI: 10.1007/s11325-016-1346-8
|View full text |Cite
|
Sign up to set email alerts
|

Gender, nocturnal hypoxia, and arousal influence brainstem auditory evoked potentials in patients with obstructive sleep apnea

Abstract: Moderate and severe OSAS patients showed abnormal BAEP which could be influenced by gender, nocturnal hypoxia, and arousal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
2
1
0
Order By: Relevance
“…Since the pathophysiological changes caused by OSA are systemic, it was reasonable that bilateral vestibular impairments resulting from OSA were synchronous and no difference. In previously published research, hearing loss ( 18 ), inner ear function ( 19 ), and brainstem auditory evoked potential ( 20 ) had been found bilateral impairments in patients with OSA, which was consistent with our findings of bilateral dysfunction of otolithic organs.…”
Section: Discussionsupporting
confidence: 93%
“…Since the pathophysiological changes caused by OSA are systemic, it was reasonable that bilateral vestibular impairments resulting from OSA were synchronous and no difference. In previously published research, hearing loss ( 18 ), inner ear function ( 19 ), and brainstem auditory evoked potential ( 20 ) had been found bilateral impairments in patients with OSA, which was consistent with our findings of bilateral dysfunction of otolithic organs.…”
Section: Discussionsupporting
confidence: 93%
“…Considering the paucity of studies investigating the BR responses in patients with OSA, further studies are needed for reaching a unequivocal conclusion, that currently cannot be postulated. However, the present data, coupled with previous studies based on evoked potentials and peripheral nerve conduction recordings, may suggest the impairment in electrophysiological conduction in patients with OSA, and that it can be possibly attributed to a hypoxic mechanism inducing myelin damage and axonal alteration [ 31 37 ]. In particular, visual and auditory evoked potentials studies showed prolonged latency and reduced amplitude of the evoked responses [ 36 , 37 ], hypothesizing a myelin damage due to intermittent hypoxia and neuro-inflammation based on delayed latency, and the occurrence of microvascular events to explain the reduced amplitude.…”
Section: Discussionsupporting
confidence: 63%
“…However, there was no correlation between AHI, mean SpO2, and auditory data as hearing threshold, TEOAe, and brainstem auditory evoked potential data. Wang et al [32], in a cross-sectional study to value the effects of sex, hypoxia, and arousal in the brainstem auditory evoked potential of OSAS patients, selected 118 individuals, of which 40 (32 males and 8 females) were affected by moderate OSAS, 44 (36 males and 8 females) were affected by severe OSAS, and 34 (22 males and 12 females) were healthy patients. Compared to the control group, women with moderate and severe OSAS had a longer latency of waves I and V, and men with moderate OSAS also had a longer latency of waves I and V, whereas men with severe OSAS had a longer latency of waves I, III, and V. Furthermore, all the possible correlations between BAEPs data with sex, age, ESS (European Social Survey) questionnaire score, AHI, ODI, MSpO2, MmSpO2, SIT90, and AI in OSAS patients have been analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Iriz et al [33] showed that repeated hypoxic events can cause multisystemic disorders in OSAS patients, even in the hearing system. Wang et al [32] evidenced some abnormalities in the brainstem auditory evoked potentials in patients with moderate and severe OSAS, obtaining longer latencies of waves I, III, and V, especially in the right ear of male patients. Ultimately, Deniz and Ersozlu [34] have demonstrated that CPAP does not improve the hearing function of OSAS patients, but it has no negative effects too, due to a possible barotrauma.…”
Section: Oxidative Stress and Auditory Systemmentioning
confidence: 99%